Increasing important roles of child and adolescent psychiatrists in the treatment of gaming disorder: Current status in Japan - Tateno, Masaru; Matsuzaki, Takanobu; Takano, Ayumi; Higuchi, Susumu (Frontiers in Psychiatry, 2022)
Background: Digital gaming is the most common leisure activity among children and adolescents in Japan, especially in males. Playing online gaming has become more common among school-age children over the years. As a result, excessive online gaming in younger children has become a significant social problem in Japan. At medical institutions having child and adolescent psychiatry services, there is an increasing number of children and adolescents with various problems related to excessive gaming. The aim of this study was to investigate the current practice of gaming disorder (GD) in clinical settings in Japan. Methods: The subjects of this study were all of 414 child and adolescent psychiatrists certified by the Japanese Society for Child and Adolescent Psychiatry. The study questionnaire was mailed to all subjects. The questionnaire consisted of 14 questions regarding gaming disorder. Results: We received 159 responses. The most common reason for a visit to child and adolescent psychiatry service which results in a subsequent diagnosis of game disorder was school refusal/absenteeism followed by disruption of sleep-awake rhythm. The most common specialized treatment for gaming disorder currently offered at child and adolescent psychiatry service is individual psychotherapy. The two most frequently experienced difficulties in the treatment of gaming disorder were low motivation to achieve recovery and a large variety of combined problems other than excessive gaming itself. With regard to the three most common psychiatric comorbidities of gaming disorder, they were autism spectrum disorder, attention deficit hyperactivity disorder, and depression. Discussion: The results of our survey revealed that although gaming disorder is a behavioral addiction, many patients with gaming disorder first visit child and adolescent psychiatry clinics rather than specialized clinics for addiction. Because it is known that gaming disorder is more prevalent among young males, including junior high and high school students, gaming disorder has already become one of the most important issues in clinical practice of child and adolescent psychiatry. Our results suggest that long-awaited clinical guidelines for gaming disorder are in order so as to ensure child and adolescent psychiatrists can provide timely standardized, but also individualized treatment for their patients.